Ex vivo evaluation of a restoration protocol for teeth with simulated incomplete rhizogenesis = Evaluación ex vivo de un protocolo de restauración para dientes con rizogénesis incompleta simulada - Retana Lobo, Cristina 1987-
The use of phosphate buffered saline (PBS) as an intracanal medication triggers a biomineralization process within mineral trioxide aggregate (MTA) apical plugs during the apexification process in teeth with incomplete rhizogenesis. However, no consensus is available in the literature regarding a restorative protocol for this type of treatment. Thus, the objective of this study was to use scanning electron microscopy (SEM) to evaluate the processes of biomineralization and adhesion in a restorative protocol for teeth with simulated incomplete rhizogenesis. Methodology: Root sections with a thickness of 2mm and cavities with a diameter of 2mm were used. The sections were randomly prepared and filled with the following materials: Group 1 (n=12), ProRoot MTA; and Group 2 (n=12): MTA Exp. Subsequently, the samples were immersed in PBS for 35 days. Every 5 days, the PBS was replaced, and the precipitates were collected, dried, and weighed. Two samples from each group were analyzed by SEM. Moreover, 24 single-rooted teeth were standardized, incomplete rhizogenesis was simulated, and 5-mm-long apical plugs were created with Pro Root MTA. As an intracanal medication, PBS was used for different periods of time: Group 1:48 h; Group 2:7 days; and Group 3:15 days. Then, fiberglass posts were cemented with the REBILDA® Post System. The samples were prepared and analyzed by SEM. Results: ProRoot MTA and MTA Exp effectively promoted the formation of carbonated apatite precipitates and biomineralization with dentin. ProRoot MTA yielded more carbonated apatite precipitates compared to MTA Exp (p=0.0536). The use of PBS as an intracanal medication for 7 and 15 days promoted intratubular mineralization (MIT), and treatment for 15 days was more effective (p < 0.05). The REBILDA® Post System effectively promoted the microimbrication of the adhesive system and the formation of resinous tags with lateral adhesive branches. Conclusion: Apexification with MTA associated...